(untitled) (Romano-arabica, 2025)
This study focuses on two verbs issued from the triliteral verbal root /l/ /g/ /y/ and their polysemous nature in Sudanese Arabic, which is analysed and described through examples. This study resulted from a qualitative observation, and the data was gathered by the author by taking part in discussions involving native Sudanese speakers2 resident in Paris and by listening to phone conversations involving some of them and their families in Sudan. Those observations allowed the documentation of the meanings associated with this verbal root, from which four Sudanese Arabic verbs arise: ligā, lāga, itlāga and istalga, with the last two having only one meaning each; therefore, this study will only focus on the verbs ligā and lāga, which showed an interesting polysemous character. Two broad semantic categories have been identified for the meanings associated with these verbs: lexical meanings (“to find” for ligā and “to meet” for lāga, also attested in some other Arabic spoken varieties) and contextual meanings, which present a semantic extension, somehow associated with the notions of exposure to something and/or contact, most of the time unexpectedly.